Hubungan Persepsi Dan Sikap Dengan Perilaku Protokol Kesehatan 5m Sebagai Upaya Preverentif Covid 19 Pada Civitas Akademika Di Universitas Malahayati Bandar Lampung - Andoko Andoko; Eka Trismiyana; Noby Amukti Sujito (Malahayati Nursing Journal, 2022)
ABSTRACT Lampung Province itself the number of cases of covid 19 as of December 2020 has reached 4,871 patients who have been confirmed to have covid 19 (Lampung Provincial Health Office, 2020). As for the details of 78 new cases, namely in Bandarlampung City 33 cases; South Lampung Regency 15 cases; East Lampung 8 cases; and North Lampung 5 cases. Then, there were 2 cases in Tulang Bawang Regency; Pringsewu 3 cases; 2 cases bid; West Coast 1 case; West Lampung 3 cases; and Central Lampung 6 cases. It is known that the relationship between perceptions and attitudes and perceptions with the behavior of the 5M health protocol as a COVID 19 preventive effort in the Academic Community at Malahayati University. The type of research is quantitative, the research design is analytic survey with a cross sectional approach. The sample in this study is part of the community at Malahayati University as many as 362, sampling using purposive sampling, and univariate and bivariate data analysis using chi square statistical test. Negative category perception as many as 217 respondents (59.9%), negative category attitude as many as 183 respondents (50.6%), behavior category applying as many as 228 respondents (63.0%), p-value 0.000 (≤0, 05) which means that there is a relationship between perception and behavior of the 5M Health Protocol as a Covid 19 Preventive Effort, the p-value is 0.000 (≤0.05), which means that there is a relationship between attitude and behavior with the 5M health protocol as a COVID 19 preventive measure. The results of the chi-square test obtained a p-value of 0.000 (≤0.05), which means that there is a relationship between perceptions and behavior of the 5m Health Protocol as a Covid 19 Preventive Effort in the Academic Community at Malahayati University Bandar Lampung in 2021. The results of the chi-square test obtained a value of p-value 0.000 (≤0.05) which means that there is a relationship between attitude and behavior of the 5M Health Protocol as a COVID 19 Preventive Effort in the Academic Community at Malahayati University, Bandar Lampung in 2021. To the campus, especially Malahayati University, Bandar Lampung, to add to the disaster management curriculum in every existing study program.  Keywords: Perception, Attitude, Behavior, 5M Protokol Protocol ABSTRAK Provinsi Lampung sendiri angka kejadian covid 19 per Desember 2020 telah menginjak angka 4.871 pasien yang terkonfirmasi mengalami covid 19 (Dinkes Provnsi Lampung, 2020) Adapun rincian 78 kasus baru yakni di Kota Bandarlampung 33 kasus; Kabupaten Lampung Selatan 15 kasus; Lampung Timur 8 kasus; dan Lampung Utara 5 kasus. Lalu, Kabupaten Tulang Bawang 2 kasus; Pringsewu 3 kasus; Pesawaran 2 kasus; Pesisir Barat 1 kasus; Lampung Barat 3 kasus; dan Lampung Tengah 6 kasus. Diketahui hubungan persepsi dan sikap dan persepsi dengan perilaku protokol kesehatan 5M sebagai upaya preverentif COVID 19 pada Civitas Akademika di Universitas Malahayati. Jenis penelitian adalah kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional, Sampel dalam penelitian ini adalah sebagian civitas di Universitas Malahayati sebanyak 362, pengambilan sampel menggunakan purposive sampling, dan analisa data univariat serta bivariat menggunakan uji statistik chi square. Persepsi kategori negatif sebanyak 217 responden (59,9%), sikap kategori  negatif  sebanyak 183 responden (50,6%), perilaku kategori menerapkan sebanyak 228 responden (63,0%),  nilai p-value 0,000 (≤0,05), nilai p-value 0,000 (≤0,05). Ada Hubungan Persepsi Dengan Perilaku Protokol Kesehatan 5m Sebagai Upaya Preverentif Covid 19 Pada Civitas Akademika Di Universitas Malahayati Bandar Lampung Tahun 2021 dan ada Hubungan Sikap  Dengan Perilaku Protokol Kesehatan 5M Sebagai Upaya Preverentif COVID 19 Pada Civitas Akademika Di Universitas Malahayati Bandar Lampung Tahun 2021.Kepada pihak kampus khususnya Universitas Malahayati Bandar Lampung untuk menambah kurikulum manajemen bencana di setiap program studi yang ada. Kata Kunci      : Persepsi, Sikap, Perilaku, Protokol 5M